Durian Kawan Aceh Selatan تطبيق طريقة الغناء لترقية قدرة الطلبة على حفظ التصريف بمعهد روضة السنة الولية - Suhaimi, Suhaimi; Abdullah, Abdullah; Sukmawati, Firli (لســـانـنــا (LISANUNA): Jurnal Ilmu Bahasa Arab dan Pembelajarannya, 2024)
The problem in learning Sharaf in the Ma'had Raudatussunnah Al-Waliyyah Tajhizi (أ) class is that there is no use of a special method for memorizing tashrif, therefore students are unable to memorize tashrif sequentially and mixing one wazan with another. This research aims to identify the effectiveness and response of students to the application of the singing method to improve students' ability to memorize tashrif. The research method used is an experimental method with a model One Group Pre-Test Post-Test Design and Researchers used pre-test, post-test and questionnaire questions as instruments in collecting data. The results of applying this method are effective in improving students' ability to memorize tashrif, based on the results of the Paired Sample T-Test with a significance level of sig. (2-tailed) 0.000 is smaller than the significance level of 0.05, which indicates that the Alternative Hypothesis (Ha) is accepted and the Null Hypothesis (H0) is rejected. The results of student responses to the application of this method were positive, where researchers obtained 72% positive responses and 28% negative responses.